The Relationship Between Family Support And Quality of Life of Cervical Cancer Patients in Rumah Singgah Sasana Marsudi Husada Indonesia - Yumni, Fathiya Luthfil (Critical Medical and Surgical Nursing Journal, 2023)
Introduction: Patients with cervical cancer are in need of support from people around them, especially families, sometimes they need hospital treatment also required encouragement and motivation of family members to reduce psychological burden and quality of life of patients with cancer increases. The purpose of this research is to determine the relationship between family support and quality of life of cervical cancer patient at Rumah Singgah Sasana Marsudi Husada Yayasan Kanker Indonesia (YKI), East Java, Indonesia. Methods: The research design used correlation analysis with cross sectional study design. Thirty patients with cervical cancer were involved through purposive sampling technique. The independent variable was family support and dependent variable was quality of life. The instrument used in this research was the WHOQOL-BREF questionnaire. The data were analyzed by Spearman Rank (Rho) test with α < 0.05. Results: Statistical result showed that family support significantly relate to quality of life of cervical cancer patient with a value of p = 0,000 and correlation coefficient (r)  = 0,994 which means it has a strong relationship. Conclusion: There is a positive and strong relationship between family support and the quality of life of cervical cancer patients. The higher the family support, the better the quality of life felt by cervical cancer patient. All staffs of the institution or foundation is expected to encourage families to support and care for sick family members (cervical cancer patient). Thus, health workers must also enhance their knowledge and skills to detect any changes in the life situation (especially family support) experienced by cancer patients, because this will affect their quality of life.